2017
DOI: 10.1021/acsami.7b14614
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Nanoparticle Assembly by a Modulated Photo-Induced Microbubble for Fabrication of Micrometric Conductive Patterns

Abstract: The laser-induced microbubble technique (LIMBT) has recently been developed for micro-patterning of various materials. In this method, a laser beam is focused on a dispersion of nanoparticles leading to the formation of a microbubble due to laser heating. Convection currents around the microbubble carry nanoparticles so that they become pinned to the bubble/substrate interface. The major limitation of this technique is that for most materials, a noncontinuous deposition is formed. We show that continuous patte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
95
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 68 publications
(97 citation statements)
references
References 28 publications
2
95
0
Order By: Relevance
“…Then, a micro droplet (10 µL) of the colloidal dispersion is placed on the electrodes. We use modulated‐LIMBT in order to bridge the gap between the gold electrodes with the Pd 0.9 Ni 0.1 NPs. The laser beam is focused at the liquid/substrate interface.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, a micro droplet (10 µL) of the colloidal dispersion is placed on the electrodes. We use modulated‐LIMBT in order to bridge the gap between the gold electrodes with the Pd 0.9 Ni 0.1 NPs. The laser beam is focused at the liquid/substrate interface.…”
Section: Resultsmentioning
confidence: 99%
“…This method is referred to as the laser induced microbubble technique (LIMBT). Lately, Armon et al have shown that modulation of the laser significantly improves the control over the microbubble and the pinning of materials, and could be used for formation of continuous conductive micropatterns. Here we show for the first time how modulated‐LIMBT is used to micropattern NPs for fabrication of hydrogen sensors.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, photothermally directed assembly has a limited resolution of micro or sub‐micro scale. [ 43,44 ] Therefore, the development of a broadly applicable, highly scalable, high throughput, and high resolution printing technique is highly desirable.…”
Section: Figurementioning
confidence: 99%
“…Control over the shape and porosity of polymeric colloids is a major goal [1], as these two properties have powerful influence over the packing of the colloids [2], deposition upon solvent evaporation [3], and emulsion stabilization [4]. Anisotropic particles can be used for biomedical applications [5,6,7], and the assembly of colloids to colloidal microstructures [8,9,10,11] could be useful for the formation of new functional materials [12]. These particles serve as building blocks for creating complex colloidal structures [13], cubic crystals [14], and staggered linear chains [15].…”
Section: Introductionmentioning
confidence: 99%